Is the Global Competitiveness Index a reliable tool for the design of labor market policies? Evidence from Peru - Celia P. Vera; Sílvio Rendón (Institute of Labor Economics (IZA), 2021)
Peru's national policy on productivity and competitiveness relies on the Global Competitiveness Index (GCI) by the World Economic Forum. We analyze the subjective component of GCI and show that, in the labor market area, this index has been largely constructed with opinion data coming from a particular group of the business sector. The opinion data is based on a survey of 98 business executives, which mainly represent firms with 100 or more employees and account for only 1% of total firms in Peru. Further, the questionnaire exhibits obvious flaws, and the underlying viewpoint that less employment protection promotes productive and formal work is not aligned with the evidence. Thus, we do not find that GCI provides a solid base for policy advice.
Keywords: J08; J32; O43; 330; labor markets; competitiveness; subjective data